Attitudes of General Practitioners Toward Prescription of Mobile Health Apps: Qualitative Study - Sarradon-Eck, Aline (JMIR Mhealth Uhealth, 2021)
BACKGROUND: Mobile health (mHealth) apps are a potential means of empowering patients, especially in the case of multimorbidity, which complicates patients’ care needs. Previous studies have shown that general practitioners (GPs) have both expectations and concerns regarding patients’ use of mHealth apps that could impact their willingness to recommend the apps to patients. OBJECTIVE: The aim of this qualitative study is to investigate French GPs’ attitudes toward the prescription of mHealth apps or devices aimed toward patients by analyzing GPs’ perceptions and expectations of mHealth technologies. METHODS: A total of 36 GPs were interviewed individually (n=20) or in a discussion group (n=16). All participants were in private practice. A qualitative analysis of each interview and focus group was conducted using grounded theory analysis. RESULTS: Considering the value assigned to mHealth apps by participants and their willingness or resistance to prescribe them, 3 groups were defined based on the attitudes or positions adopted by GPs: digital engagement (favorable attitude; mHealth apps are perceived as additional resources and complementary tools that facilitate the medical work, the follow-up care, and the monitoring of patients; and apps increase patients’ compliance and empowerment); patient protection (related to the management of patient care and fear of risks for patients, concerns about patient data privacy and security, doubt about the usefulness for empowering patients, standardization of the medical decision process, overmedicalization, risks for individual freedom, and increasing social inequalities in health); doctor protection (fear of additional tasks and burden, doubt about the actionability of patient-gathered health data, risk for medical liability, dehumanization of the patient-doctor relationship, fear of increased drug prescription, and commodification of patient data). CONCLUSIONS: A deep understanding of both the expectations and fears of GPs is essential to motivate them to recommend mHealth apps to their patients. The results of this study show the need to provide appropriate education and training to enhance GPs’ digital skills. Certification of the apps by an independent authority should be encouraged to reassure physicians about ethical and data security issues. Our results highlight the need to overcome technical issues such as interoperability between data collection and medical records to limit the disruption of medical work because of data flow.